Development and Dissemination of a Neurology Palliative Care Curriculum: Education in Palliative and End-of-Life Care Neurology. Issue 2 (April 2022) - Kluger, Benzi M.; Kramer, Neha M.; Katz, Maya; Galifianakis, Nicholas B.; Pantilat, Steven; Long, Judith; Vaughan, Christina L.; Foster, Laura A.; Creutzfeldt, Claire J.; Holloway, Robert G.; Sillau, Stefan; Hauser, Joshua
Abstract : Despite increasing awareness of the importance of a palliative care approach to meet the needs of persons living with neurologic illness, residency and fellowship programs report meeting this educational need due to a limited pool of neuropalliative care educators and a lack of adequate educational resources. To meet this need, a group of experts in neuropalliative care and palliative medicine leveraged resources from the Education in Palliative and End-of-life Care (EPEC) program and the National Institutes of Nursing Research to create a library of modules addressing topics relevant for neurology trainees, palliative medicine fellows, and clinicians in practice. In this article, we describe the development and dissemination plan of the EPEC Neurology program, initial evidence of efficacy, and opportunities for neurology educators and health services researchers to use these resources.